Utilization of sewage sludge molten slag as aggregate substitute in asphalt mixtures - Mohd Jakarni, Fauzan; Md. Yusoff, Nur Izzi; Wu, Jiantao; A. Aziz, Md. Maniruzzaman (Penerbit Universiti Teknologi Malaysia, 2015)
Sewage sludge is one of the final products from wastewater treatment processes. Handling and disposal of sewage sludge has become one of the major economic and environmental concerns. Instead of simply treating and disposing, high temperature melting treatment is considered as one of the effective alternative efforts to utilize sewage sludge as reusable materials. High temperature melting is defined as the method of melting sewage sludge at temperature of about 1500°C before cooling the molten sludge to become solidified materials, known as molten slag. Past studies have shown that high temperature melting treatment could convert sewage sludge into reusable products without adverse environmental effects. The objective of this study is to evaluate the possible utilization of sewage sludge molten slag as aggregate substitute in asphalt mixtures for pavement construction applications. The whole concept of this study was designed to assess the materials characteristics and suitability, and thus to evaluate the performance of asphalt mixtures with sewage sludge molten slag as aggregate substitute in terms of Marshall stability and flow tests. Based on the conducted study, it can be concluded that sewage sludge molten slag fulfilled almost all the standard requirements for aggregates in asphalt mixtures and can be utilized as partial replacement for aggregates. Sewage sludge molten slag has shown to be able to resist wear, polishing effect and weathering actions.